Dynamics of the range of Cytisus scoparius (L.) Link (Fabaceae) in Eastern Europe (Ukraine and Belarus) - Melnyk, Victor; Baransky, Alexander; Savchuk, Sergey; Dubovyk, Dmitryi; Leostrin, Artem; Melnyczenko, Natalia (Ecological Questions, 2022)
Regularities of dynamics of geographical didstribution of Scotch broom (Cytisus scoparius (L.) Link., Fabaceae) in the East European plain (Ukraine, Belorus) over the past 200 years are established. This species absent in floristic reports of XIX century, so for at that time it was not the component of native flora of this region. It was a cultivated species in forestries for wild animals forage. From places of cultivation C. scoparius was penetrated to natural ecosystems, occupying the niches in outskirts of forest massives, forest openings, forest cultivated coenoses, in ecotons between forests and ploughed fields, along forest rouds and paths. The rate of migration of C. scoparius increase in XX century and especially in XXI century in connections with getting warmer of climate and intensive anthropogenic change of environment (wood felling on a mass scale, absence of treatnunt on a vast places of ploughed fields, presents of many open pits and dumps of rocks, where C. scoparius found suitable habitats). Strong frost and drought are slow down, but do not stop migrating of C. scoparius in East. Inclution C. scoparius in Red Date Book of former Soviet Union was mistakenly.